Comparison Of Google Earth Engine- Based Machine Learning Classifiers For Mapping Aquaculture Ponds In Sungai Udang, Penang - Rajandran, Arvinth (2023)
This study aims to evaluate the performance of different built-in machine learning classifiers such as Random Forest (RF), Support Vector Machine (SVM), and Classification and Regression Trees (CART) to map aquaculture ponds over Sungai Udang, Penang.